Prevalence of Nematodiasis in Omasum and Abomasum of Goats Slaughtered at Pegirian Surabaya Slaughter House Through Gatrointestinal Surgery Method - Dewi Mariyam; Sri Mumpuni Sosiawati; Kuncoro Puguh Santoso; Setiawan Koesdarto; Sarmanu Sarmanu; Ira Sari Yudaniayanti (Journal of Parasite Science (JoPS), 2018)
The purpose of this research is to determine the kind of nematodes and to determine the prevalence result. Thirtysix samples of omasum and abomasum were collected from RPH Pegirian from September-November 2017 then using gastrointestinal surgery to get fresh adult worm, afterwards using Semichen-Acetic Carmine stainning method to makes the object easy to microscopic identify. The result showed that species was found Haemonchus contortus, as an identify result show that adult worm has a character on a anterior part called cervical papilae, female  worm has a barber’s pole on body also posterior part has a vulva flap, posterior part of male worm has a bursa copulatrix, spicula, gubernaculum and dorsal rays looks like Y shape. Seventeen positive samples and the prevalence rate was 47,2%, 273 adult worms and female worms 215 (78,75%) and the male worms 58 (21,25%). Chi-Square statistical test (P <0.05) showed that 13 positive samples of kambing kacang (65%) were higher infected Haemonchosis infection than 4 potitive samples of PE (25%).